Competition of Legal Systems and Harmonization of European Private Law New Paths in a Comparative Perspective - Alpa, Guido (Sellier european law Publishers, 2013)
The Rome I Regulation creates a common regime of conflict of law rules for international contract law for the EU Member States. The second volume of the selp series of Pocket Commentaries provides an article-by-article commentary which explains the underlying concepts and suggests solutions for problems that have arisen or may arise in the application of the regulation and, thus, assists in updating your knowledge with ease.